Comparison of Hub and Home Mode Learning: An Action Research from Philippines - Arnel Perez (Research Synergy Foundation, 2021)
Recent studies underscored the different actions of the Higher Educational Institutions (HEI’s) all over the world in securing the health of the students as well as the academic personnel, and likewise in mitigating the spread of coronavirus or COVID-19. Most of HEI’s closed the schools in March 2020 and shifted their paradigm from face-to-face to distance or remote learning. Mabalacat City College (MCC) as one of the HEI’s in the Philippines resolved this concern through its innovative flexible learning. In the flexible learning of MCC, the students were given options to choose between the Hub mode (modular type) and Home mode (online class). The respondents in this action research were 310 students enrolled in the course “The Life and Works of Rizal”, wherein the 230 (74.19%) of the respondents were from the Home mode of learning and the 80 (25.81%) of the respondents were from the Hub mode of learning. The finding in this study confirmed that the students in the Home mode of learning surpassed the performance of the students who were in Hub mode of learning.